Oropouche infection in Peruvian patients: A systematic review and meta-analysis - Darwin A. León-Figueroa; Edwin Aguirre-Milachay; Milagros Diaz-Torres; Jean Pierre Villanueva-De La Cruz; Edwin A. Garcia-Vasquez; Virgilio E. Failoc-Rojas; Mario J. Valladares-Garrido (PLoS ONE, 2025)
Background The Oropouche virus (OROV), discovered in 1955, has evolved from being a pathogen limited to the Amazon basin to becoming a growing threat to public health in Latin America. Because its symptoms are similar to those of dengue and zika, diagnosis is complicated. In this context, the objective of this study is to determine the prevalence of epidemiological and clinical characteristics in Peruvian patients diagnosed with Oropouche. Methods A systematic review and meta-analysis were performed in accordance with PRISMA guidelines. An exhaustive literature search was conducted up to April 10, 2025, across ten databases using MeSH terms like “Oropouche” and “Peru,” combined with Boolean operators. Only observational studies conducted in Peru that reported confirmed OROV infections through reverse transcription polymerase chain reaction (RT-PCR) or enzyme-linked immunosorbent assay (ELISA), and that described clinical or epidemiological characteristics, were included. The methodological quality of these studies was evaluated using the JBI-MAStARI tool. To estimate the pooled prevalence and 95% confidence intervals, random-effects models were applied in R (version 4.2.3). Heterogeneity was assessed using the I² statistic, and publication bias was evaluated through funnel plots and Egger’s test, when applicable. Results Six observational studies published between 2010 and 2020 were included, involving 396 Peruvian patients diagnosed with OROV by RT-PCR or ELISA. The studies were conducted in Piura, Loreto, Huánuco, Madre de Dios, and San Martín. Most patients were between 20 and 30 years old; 44.9% were male. All studies were of moderate quality. Due to the limited number of studies, publication bias was not assessed. The most common symptoms were fever, headache, myalgia, arthralgia, and retro-ocular pain. Conclusion The findings of this study reveal a significant occurrence of diverse symptoms in Peruvian patients infected with OROV. Due to the clinical resemblance to other arboviruses, it is essential to establish more precise diagnostic methods to prevent misdiagnosis and underreporting. The existing evidence remains limited, highlighting the importance of enhancing epidemiological monitoring, improving diagnostic tools, and creating public health strategies specifically targeted at endemic regions to reduce the effects of this emerging infection.